Pedagogical Conditions for Forming Competence in Future Specialists - Erkin, Nurmatov; Umida, Tursunova; Lola, Aripjanova; Oksana, Kostina; Dilfuza, Kuzikulova (International Journal of Psychosocial Rehabilitation, 2020)
The article touches upon the problem of the practical creation of pedagogical conditions for the formation of students’ professional competence. The author considers a pedagogical process as a complete phenomenon in which all components are closely interconnected and their realization influences the result – training of highly professional specialists.